Eksplorasi Aplikasi Memrise dalam Meningkatkan Kemampuan Dan Motivasi Menghafal Kosakata Bahasa Arab - Ulhaq, Aulia (Mahira: Journal of Arabic Studies & Teaching, 2025)
The limited availability of Arabic language learning media poses a significant obstacle to enhancing students’ motivation in memorizing vocabulary. This issue is particularly concerning in today’s digital era, as it has the potential to lower students’ Arabic language proficiency. However, digital media is not always a guaranteed solution for improving vocabulary memorization skills. This study aims to explore the use of the Memrise application as a solution to enhance students’ motivation in memorizing Arabic vocabulary, as well as to evaluate its effectiveness as a vocabulary memorization tool. The results indicate that using Memrise is effective in increasing the motivation of students at MTs Insan Qurani Aceh Besar to memorize Arabic vocabulary. This is supported by descriptive analysis showing that 87.5% of students rated the use of Memrise as “enjoyable” in boosting their motivation. Furthermore, the analysis of Pre-Test and Post-Test scores using the Paired Sample T-Test yielded a significance value of 0.015, which is less than 0.05. This confirms that the Memrise application is effective in helping students memorize vocabulary. The implications of this research may serve as a foundation for further development in enriching Arabic learning media within digital education environments.